Analysis of the Manuscript Entitled "Twilight with Two Bats" by Kridjomulyo Based on Drama Structure Theory - Dini Ananda Defi (Research in Education, Technology, and Multiculture, 2022)
Abstract: This research was conducted so that readers get information and knowledge about the merits and demerits of a drama script, so that readers can understand and have provisions that can later be used when asked to make a good and correct drama script. This study uses a descriptive qualitative research method. In this article, an analysis that focuses on drama scripts based on the theory of drama structure will be presented. This study uses a drama script entitled "Senja dengan Dua Kelelawar" by Kridjomulyo.   Keywords: Script, drama, regret, structure